Development of the cattle raising sector on the long term from the perspective of trade with live animals - Mariana Grodea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
In the period 2003-2017, Romania's exports of live cattle significantly increased, both in the intraCommunity area (twice) and mainly in the extra-Community area (9 times). The import from the intra-Community area, mainly consisting of reproduction animals doubled in the period 2007-2017, as against the pre-accession period. From the food security perspective, beef is not a traditional product in the Romanian consumers' diet, yet with its share of 9.3% in total meat consumption structure in the year 2016, it is an important product for dietary diversification. Of course we cannot speak for the moment about a beef market in Romania that can constantly absorb the domestic beef production at profitable prices, yet the foreign demand is sufficient for the Romanian farmers to continue and initiate new investments on beef farms. From this point of view, the paper intends to identify new development opportunities for the sector on the long term, both for relaunching domestic production and consumption increase and for creating export availabilities.
Keywords: Q10; Q13; Q19; 330; trade with bovines; herds; production